URBAN CLIMATE ACTION PLANS IN THE AGE OF CRISIS: PATHWAYS TO SUSTAINABLE AND RESILIENT CITIES - GÖKSOY SEVİNÇLİ, Berfin; TURAN, Menaf (Journal of process management and new technologies, 2025)
Cities are at the forefront of both contributing to and being affected by climate change. In order for cities to achieve sustainability and resilience, they need to develop policies against climate change. At this point, climate action plans come to the fore. This study investigates how urban climate action plans integrate risk management into spatial planning to promote sustainability and adaptive capacity. Focusing on five metropolitan cities (Bursa, Konya, Gaziantep, Copenhagen and New York), the study uses document analysis to assess mitigation targets, sectoral priorities and implementation frameworks. This study examines how local governments design and implement climate strategies within various regional and institutional frameworks. The analysis reveals a convergence around key themes such as energy transition, sustainable mobility and green infrastructure, despite administrative capacity and geographical differences. While Turkish municipalities, such as Konya and Gaziantep, have begun to emphasize climate adaptation, Bursa distinguishes itself with its relatively early strategic planning. In contrast, global cities such as Copenhagen and New York are disseminating practices against the impacts of climate change to society. By situating these examples in a comparative context, the study highlights the need for climate strategies that are both locally grounded and internationally best practice.
Keywords: Climate crisis; sustainable city; resilient city; climate action plan